The arbuscular mycorrhiza Rhizophagus intraradices reduces the negative effects of arsenic on soybean plants - Spagnoletti, Federico Nicolás (2015)
Fil: Spagnoletti, Federico Nicolás. Universidad de Buenos Aires. Facultad de Agronomía. Instituto de Investigaciones en Biociencias Agrícolas y Ambientales (INBA). Buenos Aires, Argentina.